Report of IRPA task group on the impact of the eye lens dose limits. (6th June 2017) - Cantone, Marie Claire; Ginjaume, Merce; Miljanic, Saveta; Martin, Colin J; Akahane, Keiichi; Mpete, Louisa; Michelin, Severino C; Flannery, Cynthia M; Dauer, Lawrence T; Balter, Stephen
Abstract: In 2012 IRPA established a task group (TG) to identify key issues in the implementation of the revised eye lens dose limit. The TG reported its conclusions in 2013. In January 2015, IRPA asked the TG to review progress with the implementation of the recommendations from the early report and to collate current practitioner experience. This report presents the results of a survey on the view of the IRPA professionals on the new limit to the lens of the eye and on the wider issue of tissue reactions. Recommendations derived from the survey are presented. This report was approved by IRPA Executive Council on 31 January 2017.